2022
DOI: 10.1515/nleng-2022-0269
|View full text |Cite
|
Sign up to set email alerts
|

Shear bond and compressive strength of clay stabilised with lime/cement jet grouting and deep mixing: A case of Norvik, Nynäshamn

Abstract: The strength of soil can significantly increase by stabilisation with binders. Adding binders in correct proportions to improve soil parameters is of paramount importance for earthworks. In this article, we presented a framework to explore strength characteristics of soil stabilised by several binders and evaluated using applied geophysical methods by estimated P-wave velocities. The core of our work is a systematic assessment of the effects on clay stabilisation from various binders on shear and compressive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 99 publications
0
6
0
Order By: Relevance
“…Aimed at the developing of the unified framework of clayey soil stabilization by blended binders, our study continues the research on improvement its geotechnical properties which has been observed in multiple previous publications [53][54][55][56][57][58][59]. These and other works result from the need of the improved soil properties with the addition of binders in transport infrastructure, which can be achieved by the treatment of soils with stabilising agents.…”
Section: Introductionmentioning
confidence: 60%
“…Aimed at the developing of the unified framework of clayey soil stabilization by blended binders, our study continues the research on improvement its geotechnical properties which has been observed in multiple previous publications [53][54][55][56][57][58][59]. These and other works result from the need of the improved soil properties with the addition of binders in transport infrastructure, which can be achieved by the treatment of soils with stabilising agents.…”
Section: Introductionmentioning
confidence: 60%
“…A simpler and more effective non-destructive alternative is the resonance column free-free (RC-ff) technique, which can be used to assess V p at various curing times on one specimen, and hence the strength development over time can be investigated. The applicability of this technique for soil improvement have been seen in several studies [23][24][25][26][27], however, none of these have studied the strength development over time and how this varies depending on soil and binder type, e.g., the effectiveness of different industrial by-products. One exception is the work by Lindh [28][29][30]; however, the strength difference over time for varying by-products was not studied.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, evaluating soil contamination upon stabilisation with binders is reported earlier [26][27]. Soil strength is also evaluated in the context of environmental assessment of frozen soil behaviour [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%